2004
DOI: 10.1161/01.str.0000132570.24618.78
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia, Low Folate and Vitamin B 12 Concentrations, and Methylene Tetrahydrofolate Reductase Mutation in Cerebral Venous Thrombosis

Abstract: Background and Purpose-Elevated plasma levels of homocysteine are associated with an increased risk of deep-vein thrombosis. Through a case-control study, we examined the potential association among homocysteine, folate and vitamin B 12 levels, and the common C6773 T mutation in the methylene tetrahydrofolate reductase (MTHFR) gene in patients with cerebral venous thrombosis (CVT). Methods-Forty-five patients with CVT and 90 control subjects were studied. Plasma levels of homocysteine (fasting and after methio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
87
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 31 publications
11
87
0
1
Order By: Relevance
“…In our study, CVT did not develop during the gestation or puerperal period in female cases. In populations with low folate levels and low socioeconomic status, mutation in the MTHFR gene and hyperhomocysteinemia increase the risk for IS [9,10,15,25]. In a study performed on 125 patients by Nadir et al [27], there was no correlation between high plasma homocysteine levels and C677T mutation in the MTHFR gene.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In our study, CVT did not develop during the gestation or puerperal period in female cases. In populations with low folate levels and low socioeconomic status, mutation in the MTHFR gene and hyperhomocysteinemia increase the risk for IS [9,10,15,25]. In a study performed on 125 patients by Nadir et al [27], there was no correlation between high plasma homocysteine levels and C677T mutation in the MTHFR gene.…”
Section: Discussionmentioning
confidence: 97%
“…They did not observe significant differences in the prevalence of thrombophilia between cases and control subjects or between pathogenic subtypes of IS. In another case-control study reported by Cantu et al [25], the potential association among homocysteine, folate and vitamin B12 levels and the common C677T mutation in the MTHFR gene was examined in patients with CVT. The authors also performed thrombophilic tests and reported a higher prevalence of APC-R and presence of FVL and mutation in the PT gene (G20210A) in CVT patients [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homocysteine (Hcys) is a non-essential, sulfur-containing amino acid formed during the metabolism of methionine. Mild hyperhomocysteinemia (hHcys), which occurs in approximately 5-7% of the general population, has been proved to be thrombogenic and an independent risk factor for coronary artery disease [20] , arterial and venous thrombosis [21][22][23][24][25][26] . Elevated levels of Hcys may result from abnormalities in metabolism pathways due to inherited abnormalities of the enzymes involved or nutrient deficiencies such as insufficiency of folate and vitamins B 2 , B 6 , and B 12 [27,28] .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…Its incidence is about 0.5% to 1.0% among all types of stroke [1][2][3]. There are many risk factors of CVT [1][2][3]; genetic or acquired thrombophrenia and oral contraceptive use are the most common risk factors, and hyper-homocysteinemia (Hcy) is an additional risk factor [4][5][6][7][8]. A meta-analysis of 17 clinical studies showed that oral contraceptive use, Leiden mutation of Factor V, and hyperHcy were recognized as statistically significant risk factors 8).…”
Section: Archivos De Medicina Issn 1698-9465 Journal Of Neurology Andmentioning
confidence: 99%